Social model or neoliberal champion? Economic visions of the European demos among EU citizens. Issue 4 (2nd August 2022) - Alt, Dorian
Abstract: Theories of economic nationalism have shown that identities can be constructed around various economic discourses. Yet, much of the literature focuses on official discourses while empirical tests on the citizen level are short in supply. The debate about the European demos exemplifies this shortcoming as EU institutions construct two competing visions of a European identity around economic issues. The European economy is depicted as a neoliberal competitor or as an economic space characterised by a social model. This paper investigates which of these two official visions EU citizens subscribe to. Based on 18 focus group interviews in France, Germany and Poland, I argue that citizens only share a conception of a European social model while a marriage of neoliberalism and nationalism can be detected for national economies. These findings highlight the importance of studying everyday nationhood, as not all official visions can be expected to resonate with citizens. Studies of discursive identity formation cannot only focus on official discourse, but should be flanked by investigations on the citizen level.